A one-step roll-to-roll process of stable AgNW/PEDOT:PSS solution using imidazole as a mild base for highly conductive and transparent films: optimizations and mechanisms1. Issue 22 (14th June 2015) - Kim, Seyul; Kim, So Yeon; Chung, Moon Hyun; Kim, Jeonghun; Kim, Jung Hyun
<x xml:space="preserve">Abstract</x> An AgNW/PEDOT:PSS coated, transparent, conducting, roll film (460 mm in width × 20 m in length) with good electrical and optical properties was produced using the roll-to-roll slot-die coating method.